The french chanson in the fourteenth century - Hasselman, Margaret Paine (Michigan University microfilms international, 1982)
Submitted in partial satisfaction of the requirements for the degree of Doctor of Philosophy in Music in the Graduate Division of the University of California, Berkeley, 1970